Holistic electrical machine optimization for system integration - Gerada, David; Golovanov, Dmitry; Xu, Zeyuan; Papini, Luca; Degano, Michele; Zhang, He; Gerada, C. (2017)
The power density of electrical machines required for transport applications has become a critical aspect and target of optimization. This paper looks at the development aspects of a multi-domain tool to aid for system-level optimization of electrical machines within next-generation high power-density applications. The electromagnetic, thermal and mechanical aspects are wholly integrated, thus enabling the optimization including the non-active mass. The implementation and overall architecture are described with the aim of deriving conclusions as to which SPM machine topology yields the maximum power to mass ratio.